Theoretical foundations of the creation of terminological dictionaries in language teaching. Research on the use of educational dictionaries in the educational process at the university. - Jalolov Shukhratjon Usmonovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This monograph reveals theoretical and practical issues of using various types of educational dictionaries in the educational process at the university in order to develop the speech-thinking activity of students, in particular with dictionaries of various types, as well as increasing positive motivation to learn Russian as a foreign language, as well as methodological foundations of using speech models in the educational process in order to develop communicative-speech skills and abilities of students, presentation of speech acts in order to improve the communicative abilities of students.